Early identification and monitoring of cochlear damage using extended high-frequency audiometry : a systematic review - Soer, Maggi E. (Magdalena Elizabeth) (University of Pretoria, 2022)
Dissertation (MA (Speech-Language Pathology and Audiology))--University of Pretoria, 2021.